2021
DOI: 10.6023/a20090409
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress and Challenge of Aqueous Zinc Ion Battery

Abstract: Aqueous zinc ion batteries (AZIBs) as an emerging battery energy storage technology have attracted widespread attention and developed rapidly in recent years due to the merits of high safety, low price, high energy density, environmental friendliness, easy manufacturing, etc., showing good application value and prospect in large-scale energy storage and other fields. Embarking from the current scientific issues existed in AZIBs, we review the important progress in cathode and anode materials and electrolyte us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 76 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…Considerable efforts have been dedicated to enhancing Zn anodes, such as constructing hierarchical architectures, building artificial protective layers, , and formulating electrolytes. Among them, aqueous electrolyte regulation is a convenient approach to stabilize Zn electrodes . For example, “water-in-salt” highly concentrated aqueous electrolytes have been proposed to reduce the water activity and side reactions. , In addition, designing aqueous–organic hybrid electrolytes by coupling with organic solvents (e.g., dimethyl carbonate, dimethyl sulfoxide, and antisolvents) can modulate the Zn 2+ solvation shell to decrease the number of solvating H 2 O molecules, thus alleviating the generation of byproducts.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have been dedicated to enhancing Zn anodes, such as constructing hierarchical architectures, building artificial protective layers, , and formulating electrolytes. Among them, aqueous electrolyte regulation is a convenient approach to stabilize Zn electrodes . For example, “water-in-salt” highly concentrated aqueous electrolytes have been proposed to reduce the water activity and side reactions. , In addition, designing aqueous–organic hybrid electrolytes by coupling with organic solvents (e.g., dimethyl carbonate, dimethyl sulfoxide, and antisolvents) can modulate the Zn 2+ solvation shell to decrease the number of solvating H 2 O molecules, thus alleviating the generation of byproducts.…”
Section: Introductionmentioning
confidence: 99%
“…The glutaredoxin (GRX) system is an important antioxidant system involved in various biological processes, including the oxidative stress response, DNA and protein damage repair, signal transduction, cell differentiation and apoptosis (Rouhier et al 2006;Li et al 2007;Zhang et al 2021). The GRX system includes nicotinamide adenine dinucleotide phosphate (NADPH), glutathione (GSH), glutathione reductase (GR) and GRX.…”
Section: Introductionmentioning
confidence: 99%
“…GRX can catalyse the reduction of disulfide bonds in substrate proteins through a single-or double-thiol mechanism using reduced GSH. Oxidized GSH (GSSG) is reduced to GSH by NADPH-dependent GR, thereby achieving redox cycling (Han et al 2021;Zhang et al 2021). The GRX gene has been widely studied in mammals; studies have shown that the GRX protein is closely associated with the nervous system, aging and neurodegenerative diseases, as well as the occurrence of diseases such as cancer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations